How do smart devices control and changes the lifestyle habits of human being? A study in the context of Bangladesh - Yasmin, Farhana; Hossain, Md. Alamgir (Goodwood Publishing, 2021)
Purpose: The research has been conducted to find out how the smart device is changing and controlling human’s social, cultural, and economic lifestyles. Research methodology: The study is quantitative in nature. The multiple-choice questionnaire has been prepared to collect the data from 261 respondents through the survey method using Google format and focusing on the simple random sampling technique. Here, data were analyzed through Microsoft Excel, handmade calculation. Results: The research found that respondents’ social life (71.65%), economic life (80.84%), and cultural life (79.31%) are shaped by smart devices in a positive way. Their social life (28.35%), economic life (19.16%), and cultural life (20.69%) are also shaped by smart devices in a negative way. The portion of positive change and control is more than the portion of negative. Limitations: The study is limited by sample size, geographical area, and data which are taken by using Google format instead of face-to-face interaction with respondents due to the COVID-19 pandemic. Contribution: All sorts of people will be benefited from studying this study. They will be understood how participants adopt western culture ignoring their own tradition, value system, and culture.